Electrophysical properties of polymer composites penton-silver iodide system in 8-12 GHz frequency region - Rokitsky, M.A.; Gorbyk, P.P.; Levandovsky, V.V.; Makhno, S.M.; Kondratenko, O.V.; Shut, N.I. (Functional Materials, 2007)
The heat field influence on electrophysical properties of polymer composites of the penton — dispersed silver iodide (Agl) system at volume filling from 0 to 100 % have been studied in 8-12 GHz frequency range. It has been shown that both real (ξ') and imaginary (ξ") complex dielectric permittivity components below the temperature of Agl dielectric-ionic phase transition (Tc = 420 K) depend on the content of the system components, and the imaginary component depends also on the polymer supermolecular structure. After Agl transition into ionic state, a percolation transition is observed in concentration dependences at critical percolation threshold about 30 vol.% filler content and extreme maxima about C = 50%. The ξ' and ξ" values exceed almost in wice the corresponding Agl characteristics. The results are discussed within the frame structure model.